Super-enhancer-driven lncRNA-DAW promotes liver cancer cell proliferation through activation of Wnt/β-catenin pathway - Weicheng Liang; Chuanjian Shi; Weilong Hong; Panlong Li; Xue Zhou; Weiming Fu; Lizhu Lin; Jinfang Zhang (Elsevier, 2021)
Aberrant expression of long non-coding RNAs (lncRNAs) has been reported in multiple cancers. However, the underlying mechanisms mediated by super-enhancers remain elusive. Here we sought to define the role of a novel lncRNA termed lncRNA-DAW in tumorigenesis. Our results revealed that lncRNA-DAW was driven by a liver-specific super-enhancer and transcriptionally activated by HNF4G, leading to frequent elevation in hepatocellular carcinoma (HCC) specimens. Ectopic expression of lncRNA-DAW promoted both in vivo and in vitro tumor growth. By using RNA sequencing, Wnt2 was screened out as a downstream effector of lncRNA-DAW. We next found that lncRNA-DAW physically interacted with EZH2, a negative regulator of Wnt2. This interplay subsequently potentiated CDK1-EZH2 interaction, leading to the phosphorylation and ubiquitination of EZH2. The lncRNA-DAW-mediated EZH2 degradation facilitated the de-repression of Wnt2 transcription, which eventually activated the Wnt/β-catenin pathway. Furthermore, we verified that Wnt2 potentiated in vitro and in vivo cancer cell growth by activating the Wnt/β-catenin pathway. Finally, Wnt2 amplification was confirmed as a common event in liver cancer, and the expression of lncRNA-DAW was positively correlated with Wnt2 in HCC specimens. Collectively, we are the first to identify lncRNA-DAW as a novel candidate oncogene in liver cancer, and this lncRNA may serve as a novel clinical diagnosis biomarker for liver cancer.